Predation and reproductive output of the ladybird beetle Stethorus tridens preying on tomato red spider mite Tetranychus evansi - Britto, E.P.; Gondim, M.G.C.; Torres, J.B.; Fiaboe, K.K.M.; Moraes, G.J.; Knapp, M. (Springer, 2009)
Predatory behaviour and reproductive output of the ladybird beetle Stethorus tridens Gordon as function of the tomato red spider mite (TRSM), Tetranychus evansi Baker & Pritchard, densities was investigated in the laboratory. Adult female of S. tridens were isolated in cylindrical plastic arenas, containing a leaf disc of Solanum americanum Mill. with 5, 20, 40, 60, 80 or 100 T. evansi nymphs. The number of prey consumed and eggs laid were evaluated daily for ten consecutive days, starting at the oviposition. Oviposition of S. tridens was positively correlated with prey consumption and lower threshold prey consumption for S. tridens laying eggs was 16.3 mites per day. The instantaneous rate of attack (ca. discovery area) and the handling time were 0.0062 h-1 and 0.83 h, and 0.00254 h-1 and 0.78 h, respectively, for predators at the 1st- and 10th-oviposition day. The predator exhibited a type II functional response at 1st- and 10th-oviposition day with a maximum consumption per predator of 33 T. evansi nymphs per day at the highest prey density. The ladybird beetle S. tridens is often collected associated with red spider mite colonies on solanaceous wild plants and the results suggest the potential of this ladybird beetle to control T. evansi in tomatoes crops.